INTEGRATION OF LOW EQUIPMENT AUTOMATED SYSTEM OF CONTROL FREIGHT TRAIN THE AUTOMATED CONTROL SYSTEM OF THE PASSENGER TRAFFIC, CONNECTING IT TO A SINGLE SYSTEM SOFTWARE DOCUMENTATION - Ivchenko, Yu. M.; Ivchenko, V. H.; Hondar, O. M. (Science and Transport Progress, 2009)
In the paper the integration of nodes of data transfer network for automated control systems of freight and passenger traffic is proposed. It allows more efficient using the network equipment and communication channels.